Colistin-resistance gene mcr in clinical carbapenem-resistant Enterobacteriaceae strains in China, 2014–2019 - Hong Huang; Ning Dong; Lingbin Shu; Jiayue Lu; Qiaoling Sun; Edward Wai-Chi Chan; Sheng Chen; Rong Zhang (Emerging Microbes and Infections)
To investigate whether introduction of colistin into the clinical settings selected colistin-resistant CRE, we performed molecular epidemiological study of 1868 CRE strains collected from different geographical locales in China during the period 2014–2019. 1755 (96.18%) isolates carried the carbapenemase genes blaKPC and blaNDM; 14 Escherichia coli isolates (0.75%) carrying mcr-1 and blaNDM (MCR-CREC) were also identified. Importantly, the number and relative prevalence of MCR-CREC isolates increased from 5 (0.41%) to 9 (1.38%) after introduction of polymyxin into clinical practice. Consistently, results of genetic analysis indicated that MCR-CREC strains collected before December 2017 were genetically diverse, yet those collected after that date exhibited more closely related genetic profiles, indicating that specific MCR-CREC strains were rapidly selected as a result of increased usage of colistin in clinical settings. The resistance level of MCR-CREC isolates to colistin increased after the introduction of polymyxin into clinical use with the MIC to colistin from <2 mg/L in 80% strains to 2 mg/L in 100% strains. Further dissemination of MCR-CREC strains, which exhibit resistance to the last-line drugs of carbapenems and colistin, is expected to pose a severe threat to human health.